Effects of sub-monthly and sub-daily water level variations on water level fluctuation requirements of Phragmites australis and Phalaris arundinacea - Tingyu Zhang; Wenjuan Gao; Saibo Yuan; Xiaodie Jiang; Yongjing Zhao; Yongde Cui; Hongzhu Wang (Water Biology and Security)
Water level variations (WLVs) substantially affect the spatial distribution of riparian vegetation. Accurately quantifying the water level fluctuation requirements (WLFRs) of aquatic macrophytes is essential for effective ecological water level management. Nevertheless, studies on the WLFRs of herbaceous plants in large river floodplains, such as Phragmites australis (common reed) and Phalaris arundinacea (reed canarygrass), are limited. Herein, we investigated the WLFRs of the two plants across water bodies with different WLVs in the Yangtze River Basin. We focused on the effects of sub-monthly and sub-daily WLVs on their average monthly water depth requirements (WDRs) during critical growth periods. Our findings indicated: (1) For Phragmites, during the emergence period, the upper limits of WDRs decreased with increased amplitudes of sub-monthly WLVs and with greater frequency and amplitude of sub-daily WLVs, in which sub-daily variations had a more pronounced effect. Conversely, during the rapid growth period, the upper limits increased with larger sub-monthly WLVs amplitudes, but decreased with higher frequency and amplitude of sub-daily WLVs. (2) For Phalaris, during both the emergence and rapid growth periods, intensified sub-daily WLVs led to decreased upper limits of WDRs. In summary, although distinct disparities existed in the WLFRs of Phragmites and Phalaris across various water bodies, the trends in WDRs during the emergence and rapid growth periods were consistent for both species. These findings provide essential quantitative data to restore aquatic vegetation and carry out effective ecological water level management in large-scale riparian ecosystems.